THE RELATIONSHIP OF ONLINE GAMES ADDICTION WITH TEACHING SOCIAL SKILLS IN THE COMMUNICATION SCIENCE STUDENTS OF STATE ISLAMIC UNIVERSITY OF NORTH SUMATERA - Elda Ayumi; Iskandar Zulkarnain; Yan Hendra (UIN Sumatera Utara Medan, 2019)
This research was conducted among communication science students of State Islamic University Medan of North Sumatra, the aim of this study is to determine the level of social skills in adolescents, online game addiction level, and the relationship of online game addiction with social skills in adolescents among communication science students of State Islamic University of North Sumatra. This research uses quantitative methods. Research subjects were 186 respondents who were selected using random sampling. In collecting data, researchers used a Likert scale. The analysis of data in this study uses simple linear regression. In this study, researchers used the Sociopsycholog theory from Little Jhon. The results of the research conducted, it is known that (1) the level of online game addiction in adolescents among communication science students at the State Islamic University of North Sumatra is in the medium category with a percentage of 69.4%. (2) while the level of social skills of adolescents among communication students of State Islamic University of North Sumatra Medan is in the medium category with a percentage of 85.5% or 159 subjects (3) known also (correlation coefficient 0.215 with p = 0.000 and Sig scores .2-tailed 0.05) which means that there is a significant relationship between online gaming addiction and social skills among students of communication science at the State Islamic University of North Sumatra in Medan.